The Late-Eighteenth-Century Climate of Cape Town, South Africa, Based on the Dutch East India Company “Day Registers” (1773–91) - Grab, Stefan; Williams, Mark (Bulletin of the American Meteorological Society, 2022)
We introduce the Dutch East India Company “day registers” as one of the world’s longest known pre-nineteenth-century corporate chronicles (1652–1791) containing near-continuous, systematic, noninstrumental daily weather information for Cape Town, South Africa. This transcript provides the longest-known continuous seventeenth- to eighteenth-century daily weather record for Africa and the Southern Hemisphere. An 18-yr (1773–91) climate chronology from this record is presented, thus providing unique insight to the late-eighteenth-century climate of Cape Town. Extraction of daily weather information for basic statistical analysis includes precipitation, wind, sky conditions, and accounts of storms, drought, and floods. From this, we provide monthly and annual number of rain days, a rain index (relative rainfall amount), hot and cold days, and occurrence of storm-strength winds. Results show extreme weather and climate variability in Cape Town during the mid- to late 1780s.